(3EMcGe GdSjWQI GdeGdjI YfO GdJMhd GdiGbJUGOjGJ GdShbs - (3QhfGdO(B, (3eGcjfhfs; (3UdjH HWQS(B, s ((3GdbGgQI(B:s (3GdLeYjI GdeUQjI dfTQ GdeYQaI hGdKbGaI GdYGdejI(B,s, 1996)
(3GFbI GdeGdjI h GeJGLjI QCS GdeGd h fJGhd CSYGQ aGFOI eQJaYI h MbjbjI h COhGJ GdVFbI GdeGdjI h cPG YHA GdJVNe h GdQbGHI Ydi GdfbO h GdQbGHI Ydi GdGbJUGO GdTGed CKfGA ERGdI GdJVNe h YOe ESJbQGQ GdGbJUGO GdTGed h GdeNGWQ GdCNdGbjI aj GdYed GdeUQaj h JfGhd GdMeGFjI aj GdJLGQI GdNGQLjI h SjGSI SYQ GdUQa h GdShb GdOhdjI dQCS GdeGd h GdJMQQ GdGbJUGOj ceG Je GdJWQb Gdi GdSjWQI Ydi GdGhVGY GdeGdjI EHGf aJQI GdJMhd ef GdGbJUGO GdeNWW eQcRjG Gdi EbJUGO GdShb h cPdc GdJLGQI GdNGQLjI h GdMeGjI h GdbjeI GdeVGaI GdSdHjI aj GbJUGO GTJQGcj Ydi WQjb GdJMQQ , h Gdfeh GdeGdjh GSJbQGQ GdGbJUGO GdTGed aj GdUjf (B1978-1992 (3h EecGf JWHjb Pdc aj QhSjG h ChQhHG GdTQbjI h CNjQG GdJMQjQ GdJOQjLj ebGQfI HfXjQgGdeJYLd aj GdJLGQI GdNGQLjI GdGTJQGcjI (B.s
(3eQGLY U(B.303s
Keywords: (3GdGbJUGOs